Narrative Fractures in Policy Communication: Framing and Public Sentiment on Indonesia’s Free Nutritious Meals Program - Fajar, Harry Fajar Maulana; Arroyan, Fadel (Jogjakarta Communication Conference (JCC), 2025)
The "Makan Bergizi Gratis" program, initiated by the Indonesian government and amplified by the media outlet Tempodotco, has triggered widespread public discourse. This study aims to examine how the program is framed in official media narratives and how it is received by the public. Using a multi-method textual analysis approach, the research combines keyword frequency analysis, non-negative matrix factorization (NMF) topic modeling, sentiment classification, and manual framing analysis. Two datasets were analyzed: structured video descriptions representing the official narrative, and 1,048 user comments capturing public sentiment. The results reveal a significant divergence between the two discourses. Official descriptions emphasize positive, policy-driven messages—highlighting nutritional benefits, administrative strategy, and global benchmarking. In contrast, public responses are dominated by negative sentiment, marked by skepticism, financial concerns, and political criticism. Common themes in the comments include distrust toward government implementation, humor and sarcasm (e.g., “omon-omon”), and comparisons to more established foreign programs. The sentiment analysis confirmed that over half of public comments carried negative emotional weight. These findings underscore the complexity of digital policy communication, especially in politically charged environments. The study contributes to communication research by illustrating how media framing and audience interpretation interact in digital spaces. It also highlights the necessity for more responsive and transparent public communication strategies in large-scale policy initiatives.